Penerapan Metode PDCA untuk Menurunkan Tingkat Kerusakan Mesin pada Proses Produksi Penyalutan - Cepi Kurniawan; Hery Hamdi Azwir (President University, 2019)
The coating process is the process of covering the tablet with a thin layer of substance which generally has very little effect. The process coating process uses a Driam machine and the machine has a very high utilization of 125%. The company's ability to provide additional salute machines requires time in its investment, remedial efforts to reduce the damage level of the salute machine are needed so as not to increase machine utilization, while the damages that occured in the coating process from January to December 2016 are Speed Pump, Air Flow Damper, Spray Gun, Supply Compressed Air, Steam, Pan Speed, & Wind Hose. From the background of the problem the company needed repairs that were useful to reduce the level of damage to the salute machine. These improvements are carried out using the Plan Do Check Action (PDCA) method. The PDCA method is a repetitive process improvement activity to solve a problem in quality control and is included in the Total Quality Management (TQM) in which TQM is the application of quantitative methods and human knowledge to improve materials and services which of course improves processes and efforts to meet customer satisfaction . The level of damage to the machine salute has decreased after repairs to the engine damage Pump Speed & Air Flow Damper where it eliminates 2 of 7 damage that occurs in the coating process or by 45.6% of the total damage.